2019
DOI: 10.12688/f1000research.20150.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding lipodystrophy: a focus on lipodystrophy-associated cardiovascular disease and potential effects of leptin therapy on cardiovascular function

Abstract: Lipodystrophy is a disease characterized by a partial or total absence of adipose tissue leading to severe metabolic derangements including marked insulin resistance, type 2 diabetes, hypertriglyceridemia, and steatohepatitis. Lipodystrophy is also a source of major cardiovascular disorders which, in addition to hepatic failure and infection, contribute to a significant reduction in life expectancy. Metreleptin, the synthetic analog of the adipocyte-derived hormone leptin and current therapy of choice for pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 97 publications
0
15
0
Order By: Relevance
“…Patients with CGL deficient in adipose tissue and leptin present with severe cardiovascular alterations including hypertension, coronary artery disease, hypertrophic cardiomyopathy and autonomic impairment. Despite numerous studies [ 2 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 31 ], the consequences of a generalized deficiency in adipose tissue and the subsequent decrease in circulating leptin levels on vascular function remains ill-defined. In the present study, we used a mouse model replicating the human Berardinelli-Seip congenital lipodystrophy syndrome, the Bscl2 deficient mouse [ 1 , 15 ], to characterize their vascular contractile phenotype, and studied the effects of chronic leptin supplementation as patients with CGL would receive [ 6 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients with CGL deficient in adipose tissue and leptin present with severe cardiovascular alterations including hypertension, coronary artery disease, hypertrophic cardiomyopathy and autonomic impairment. Despite numerous studies [ 2 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 31 ], the consequences of a generalized deficiency in adipose tissue and the subsequent decrease in circulating leptin levels on vascular function remains ill-defined. In the present study, we used a mouse model replicating the human Berardinelli-Seip congenital lipodystrophy syndrome, the Bscl2 deficient mouse [ 1 , 15 ], to characterize their vascular contractile phenotype, and studied the effects of chronic leptin supplementation as patients with CGL would receive [ 6 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous studies [2,[7][8][9][10][11][12][13][14]31], t quences of a generalized deficiency in adipose tissue and the subsequent decre culating leptin levels on vascular function remains ill-defined. In the present s used a mouse model replicating the human Berardinelli-Seip congenital lipod syndrome, the Bscl2 deficient mouse [1,15], to characterize their vascular contra notype, and studied the effects of chronic leptin supplementation as patients w would receive [6,11]. Using this approach, we demonstrated that CGL induced increase in vascular adrenergic contractility that is reduced by chronic leptin t We furthered our findings by demonstrating that CGL-mediated increases and duced reduction in adrenergic contractility are independent of NOS activity, dependent on Nox1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…160 In vitro investigation showed that rodent and human cardiomyocyte hyperplasia were activated by the effect of leptin. 169 Adiposity and obesity are the major risk factors for the pathogenesis of MetS, such as T2DM and hypertension, which in turn leads to cardiovascular complications, 170 because abnormality in adipose tissue and obesity induce a chronic inflammation. 55 Adiponectin/leptin ratio will be diminished during systemic inflammation to induce pathogenesis of various MetS.…”
Section: Hyperleptinemia Aggravates Further Cardiovascular Risk Complicationmentioning
confidence: 99%